Deteksi Dini Hama dan Penyakit Padi Menggunakan Metode Certainty Factor - Sulistiyanto Sulistiyanto; Tri Aristy Saputri; Noviyanti Noviyanti (STMIK Budi Darma, 2022)
Padi is one of the main food commodities. Every year the need for rice continues to increase, as fulfillment of domestic and export needs. Various efforts were made in order to increase rice production, including superior seed seed research, expansion of planting land and counseling and mentoring to farmers. Pests and diseases are one of the 'main factors that have an impact on the decline in the productivity of rice plants. Recognizing Symptoms of the disease requires skills and experience and knowledge. Symptoms that arise often by farmers are difficult to recognize and only experts who can identify it correctly and correctly. The limitations of agricultural experts in the region, are obstacles for farmers when they want to consult. The expert system can then be an alternative solution to replace the expert role in deciding the type of disease that attacks. This study aims to design an expert system using certainty factors for website-based to help farmers in deciding the type of disease. Diseases that are sampled include blast, hawar daun (kresek), busuk pelepah, tungro (kerdil), chocolate spots and striped spots. The method used in this research is Reseach And Development (RND).The results of system output testing validated by experts have an accuracy of 66.67%, and system testing with blackbox testing is declared valid to the main features of the system. It is expected that this expert system, farmers become helped in deciding the type of disease that attacks their rice and can take preventive actions so as not to spread to other rice plants